Ecological stoichiometric characteristics of Solanum rostratum organs in different habitats - Hu, Lijun; Qiu, Juan; Zhu, Xinping; Ren, Cai; Wang, Kui; Yimingniyazi, Amanula (Frontiers in Plant Science, 2025)
AimsPlant ecological stoichiometry focuses on the elemental content (such as carbon (C), nitrogen (N), and phosphorus (P)) in plant organs and its relationship with environmental factors and ecosystem functions. Alien invasive species ensure their rapid and efficient propagation by regulating their nutrient distribution, and they also influence soil physical and chemical properties by modifying the nutrient cycle and releasing allelochemicals, thus forming an environment conducive to their growth, reproduction, and diffusion. However, evidence on the ecological stoichiometry characteristics of the invasive plant Solanum rostratum and its invaded soils across different habitats in China, particularly the species’ nutrient utilization strategies in varying environments, is lacking.MethodsThis study investigated S. rostratum in Xinjiang Province of China and analyzed the organ allocation of C, N, and P and stoichiometric characteristics across four distinct habitats (irrigation ditches, riparian zones, desert steppes, farmlands) through field surveys and controlled laboratory experiments. In addition, a conceptual framework elucidating S. rostratum’s invasion mechanisms, nutrient-use adaptations, and plant-soil feedback was established.ResultsThe results demonstrated that S. rostratum exhibits significant stoichiometric adaptation strategies in different habitats, thus providing a scientific foundation for understanding its invasion mechanisms and formulating effective control measures. The results indicated that significant differences in C, N, and P content occurred among the organs of S. rostratum, with a peak in reproductive tissues (flowers, fruits).ConclusionThis priority allocation to reproduction underscores an evolved strategy for optimizing fitness. Moreover, with changes in the invasion degree of S. rostratum, the soil nutrient cycle changed, with obvious differences in the responses of different habitats. This indicates that S. rostratum invasion not only affects its own growth but also affects the nutrient cycle of the whole ecosystem by changing the soil nutrient status. In addition, habitat type had a significant impact on the element accumulation of S. rostratum, and the quantitative relationship between plant and soil elements showed obvious habitat specificity. This phenomenon reflects the driving roles of environmental stress and resource availability on plant growth. S. rostratum adjusts its element absorption and distribution strategies under the environmental and resource conditions of different habitats as an adaptation to environmental changes. Therefore, S. rostratum adapts to heterogeneous environment or heterogeneous condition. Accordingly, differentiated control strategies tailored to its invasion characteristics in distinct habitats should be formulated to enhance its control efficiency.